Environmental and Social Factors in Preventing, Assessing, and Treating Problem Behavior in Young Children. (March 2017) - Donaldson, Jeanne M.; Austin, Jennifer L.
Problem behavior (e.g., noncompliance, hitting) is common among young children but, depending on the child's environment, potentially can lead to future social, emotional, and academic problems. Research in applied behavior analysis has identified many contextual variables that support appropriate behavior and provides clear suggestions for preventing frequent and persistent problem behavior. Although many empirically supported recommendations derive from the current research base, future research needs to fine-tune some of the strategies, and policy support is required to put those recommendations in place. Specific recommendations support parents and early child care professionals/teachers in preventing, assessing, and treating problem behavior in young children.